The Distance to L∞ in the Grand Orlicz Spaces. (9th September 2013) - Farroni, Fernando; Giova, Raffaella
Abstract : We establish a formula for the distance to L ∞ from the grand Orlicz space L Φ ) Ω introduced in Capone et al. (2008). A new formula for the distance to L ∞ from the grand Lebesgue space L n ) Ω introduced in Iwaniec and Sbordone (1992) is also provided.